Accuracy of Quantification of Iodine and Hounsfield Unit Values on Virtual Monochromatic Imaging Using Dual-Energy Computed Tomography: Comparison of Dual-Layer Computed Tomography With Fast Kilovolt-Switching Computed Tomography. Issue 6 (November 2018) - Washio, Hayate; Ohira, Shingo; Karino, Tsukasa; Nitta, Yuya; Hayashi, Masaaki; Miyazaki, Masayoshi; Teshima, Teruki
Abstract : Objective: The aim of the study was to compare the accuracy of quantification of iodine and Hounsfield unit (HU) values on virtual monochromatic imaging (VMI) using dual-layer computed tomography (DLCT) and fast kilovolt-switching computed tomography (FKSCT). Materials and Methods: This study was performed in 2 phantoms (large and small) using 16 rods representing different materials (iodine, calcium, blood, and adipose tissue) with different dimensions and concentrations. The absolute percentage errors (absolute ratio of measurement error to true iodine concentration) for iodine concentration and HU value on VMI at 50, 70, and 100 keV were compared between DLCT and FKSCT. The Mann–Whitney U test was used to assess statistical significance. Results: Overall, the absolute percentage errors for iodine concentration and HU value on VMI were smaller for DLCT than for FKSCT. Conclusions: Overall, the accuracy of iodine and HU values was higher for DLCT than for FKSCT.